Neuropedagogy and neuroimaging - Antonio Hernández Fernández (Texto Livre: Linguagem e Tecnologia, 2022)
The present study is based on the assumption that there is a lack of information, both nationally and internationally, on neuropedagogy, and that there is more than enough evidence of the need for a conceptualization of neuropedagogy. Therefore, the general objective is to analyze the relationship between neuroeducation, neurodidactics, teacher training and neuropedagogy. Data collection was carried out with a 27-item ad hoc Likert scale questionnaire, reliable (Cronbach’s Alpha, .973), and validated in its content and construct with an exploratory factor analysis (KMO (.843), Bartlett (Sign.000), Determinant (9.416E-19)). The research sample was selected by convenience from among university teachers in Spain, Paraguay, Ecuador, Brazil and Mexico, with a total of 1264 participants. The research design is non-experimental, descriptive, explanatory, correlational and regression-based. The results show that the future of pedagogy must include neuropedagogy, evidencing: 1) the need of neuroeducation knowledge for Neuropedagogy; 2) the understanding of neurodidactics as the practical application for neuropedagogy, 3) the importance of neuro-orientation and neuro-educational organization, and 4) the need for the training of trainers. All of which is reinforced by the examples shown of neuroimaging that demonstrate the need for neuropedagogy and teacher training in neuropedagogy.